2020
DOI: 10.24036/jelt.v9i1.107809
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Students’ Vocabulary Mastery and Speaking Ability at Grade 8 of Junior High School

Abstract: This research aimed to find out the correlation between students’ vocabulary mastery and speaking ability at grade 8 of SMP Negeri 26 Padang. This research was quantitative research which used correlational technique design. The sample of the research was 30 students of grade eight selected by clustering sampling. The instruments used in the research were vocabulary test and speaking test. Vocabulary test consisted of 50 questions of multiple choices, and speaking test in the form of role play. The research da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…A study by Aristi, Prawati, and Maria (2016) has shown that high level of vocabulary is a strong predictor of language proficiency. Further studies by Seffar (2015); (2018); Uzer (2017) have also shown a strong correlation between vocabulary and English language proficiency. Past exploration led in the Pakistani setting gives a few experiences into the connection between vocabulary information and talking capability.…”
Section: Discussionmentioning
confidence: 90%
“…A study by Aristi, Prawati, and Maria (2016) has shown that high level of vocabulary is a strong predictor of language proficiency. Further studies by Seffar (2015); (2018); Uzer (2017) have also shown a strong correlation between vocabulary and English language proficiency. Past exploration led in the Pakistani setting gives a few experiences into the connection between vocabulary information and talking capability.…”
Section: Discussionmentioning
confidence: 90%
“…The lack of vocabulary influences student speaking passivity in social media by limiting their ability to articulate thoughts coherently, fostering uncertainty and inhibiting active Novi Aghata Nur Khamalia & Fahmy Imaniar participation due to a fear of being misunderstood or judged negatively (Uzer, 2017). The influence of a lack of vocabulary on student speaking passivity in social media is marked by its impact on effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Without having a wide range of vocabulary, someone couldn't have good speaking skills. (Sartika & Ritonga, 2020), (Putri & Refnaldi, 2020).…”
Section: The Implementation Of Yawm 'Arabi As Arabic Environment Activationmentioning
confidence: 99%